Infraclavicular brachial plexus block using nalbuphine versus midazolam as adjuvants to bupivacaine in upper limb surgery - Mohamed Abdel Gawad Abdel Halim (Wolters Kluwer Medknow Publications, 2018)
Background Brachial plexus block is a regional anesthesia technique for different surgeries in the upper limb. It is useful as a sole regional anesthesia technique or combined with general anesthesia. The adjuvants to local anesthetics may be improving the quality and duration of analgesia of the brachial plexus block. Objective To evaluate the efficacy of nalbuphine and midazolam as adjuvants to bupivacaine in the infraclavicular brachial plexus block. Patients and methods The study was carried out on 70 patients of the American Society of Anesthesiologist, physical status I, II of both sexes, 20-60 years old and scheduled to forearm and hand surgeries. The patients were classified into three equal groups. Group B: using 20 ml of bupivacaine (3 mg/kg) with 1 ml of saline. Group M: using 20 ml of bupivacaine (3 mg/kg) with midazolam 5 mg (1 ml). Group N: using 20 ml of bupivacaine (3 mg/kg) with nalbuphine 1 ml (10 mg). Results The onset time of sensory and motor blocks were significantly shorter in the adjuvant groups N and M compared with group B. There was a significant increase in the duration of postoperative analgesia in group N compared with groups M and B. Conclusion The addition of nalbuphine and midazolam to bupivacaine in the infraclavicular brachial block improves the speed of sensory and motor onset, the quality of anesthesia, and decreases the analgesic requirements during the first 24 h postoperatively without obvious side effects. The addition of nalbuphine to bupivacaine was superior in delaying the postoperative analgesia requirement.